2018
DOI: 10.1002/stem.2859
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Prostate Cancer Stem Cells: Current Understanding

Abstract: Prostate cancer (PCa) is heterogeneous, harboring phenotypically diverse cancer cell types. PCa cell heterogeneity is caused by genomic instability that leads to the clonal competition and evolution of the cancer genome and by epigenetic mechanisms that result in subclonal cellular differentiation. The process of tumor cell differentiation is initiated from a population of prostate cancer stem cells (PCSCs) that possess many phenotypic and functional properties of normal stem cells. Since the initial reports o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 256 publications
(317 reference statements)
1
103
0
Order By: Relevance
“…The 5‐year survival rates for patients with localized PCa have grown consistently over the past decades and it is currently nearly 100%. However, majority of PCa patients with advanced PCa will eventually develop metastases, and metastatic PCa remains to be incurable …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5‐year survival rates for patients with localized PCa have grown consistently over the past decades and it is currently nearly 100%. However, majority of PCa patients with advanced PCa will eventually develop metastases, and metastatic PCa remains to be incurable …”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies revealed an important role of BRCA1 protein in regulation of the maintenance of breast cancer stem cells (CSCs) populations. The population of CSC possesses self‐renewal and differentiation properties that enable it to initiate and maintain tumor growth . A high aldehyde dehydrogenase (ALDH) activity has been considered as CSC marker in many tumor entities including PCa and a number of studies showed that expression of ALDH proteins including ALDH1A1 and ALDH1A3 is a predictor of poor clinical outcome of breast, brain and prostate cancer patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AR + /ARv7 + cell population is significantly decreased with increased Gleason grade, while the AR − /ARv7 − the population is significantly increased (Figure ). This suggests that more aggressive tumors express lower levels of AR and ARv7 than tumors that are considered less aggressive, perhaps supporting the idea of AR heterogeneity and AR‐negative clonal expansion as tumors progress . Additionally, the AR + /ARv7 + cell population is significantly decreased in tumors that become recurrent in under 5 years, while the AR − /ARv7 − the population is significantly increased (Figure ).…”
Section: Discussionmentioning
confidence: 65%
“…This suggests that more aggressive tumors express lower levels of AR and ARv7 than tumors that are considered less aggressive, perhaps supporting the idea of AR heterogeneity and AR-negative clonal expansion as tumors progress. 42 Additionally, the AR + /ARv7 + cell population is significantly decreased in tumors that become recurrent in under 5 years, while the AR − /ARv7 − the population is significantly increased ( Figure 5). This suggests the level of AR expression is an indicator of time to recurrence, perhaps due to the widespread use of therapies that directly target AR (ie, bicalutamide, enzalutamide, and VELLKY ET AL.…”
Section: Ar and Arv7 Coexpression Predicts Advanced Gs And Disease mentioning
confidence: 94%